Effect of Combined Feedback and Verbal Encouragement on Anaerobic Performance, Technical and Physiological Aspects During Small-Sided Basketball Games for Students’ Girls - Mekni, Rim; Hammami, Mohamed Ali; Sahli, Faten; Selmi, Okba; Stanica, Gabriel; Panaet, Adelina Elena; Alexe, Cristina Ioana; Trabelsi, Omar; Ben Ezzeddine, Lamia (International Journal of Sport Studies for Health, 2024)
Objective: The aim of this research is to determine the effect of combined feedback and verbal encouragement on anaerobic performance, technical and physiological aspects during small-sided Basketball games for adolescent schoolgirls. Material and Methods: Sixty schoolgirls were divided into 3 groups of 20 girls: control group (G1) (mean ± standard deviation (M±SD); age:15.45 ± 0.41years), verbal encouragement group (G2) (M±SD; age:15.65 ± 0.61years) and combined feedback and verbal encouragement group (G3) (M±SD; age:15.55 ± 0.51 years). Muscle power (countermovement jump (CMJ); 5-Jump-Test (5JT)), agility (Illinois-test), sprint speed (10 and 30 m)]; technical skill and heart rate (HR) responses during 3 vs. 3 small sided basketball game (SSBG) were measured. Additionally, HR was continuously recorded and video analysis was used to quantify technical actions during SSBG. Results: The results showed greater improvements in muscle power of CMJ and 5JT for G3 compared to G2 (P<0.001, ES=1.21, moderate, p<0.001, ES= 4.74, large, respectively) and for G3 compared to G1 (P<0.001, ES= 1.72 large; p=0.001, ES =6.86 large respectively). The time in the 10 m, 30 m sprints and agility decreased more profoundly for G3 compared to G2 (p<0.001, ES=4.93, large; p<0.001, ES=3.27, large, p<0.001, ES=1.14, large, respectively).For technical skill, the ball contacts, successful balls, number of shots and successful shots were higher in G2compared with G1 (p<0.001, ES=1.48 moderate; p<0.001, ES=3.83, large; p<0.001, ES=1.99, large; p=0.001, ES=2.41, large respectively), higher in G3 compared with G2 (p<0.001,ES=-0.89, large, p=0.001, ES=-1.48 moderate; p=0.001, ES= 3.97, large; p<0.001, ES=4.93, large, respectively). Furthermore, average heart rate was higher in G3 compared with G2 and G1 (p<0.001, ES = 1.06, large; p<0.001, ES=4.64, large, respectively). Conclusion: These findings indicate that the combination of feedback and verbal encouragement are more effective for achieving better results in physical fitness and technical skill than verbal encouragement group and control group.